2019
DOI: 10.1093/jbcr/irz069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraoperative Dexamethasone Administration in Adult Diabetic Burn Patients

Abstract: The steroid dexamethasone is used intraoperatively to prevent postoperative nausea. Studies of intraoperative steroid use in diabetic patients have shown conflicting effects on blood glucose and complications, and their use has not yet been studied in the burn population. A review of adult diabetic acute burn patients undergoing surgery at a verified burn center from 2012 to 2017 was conducted. Statistical analysis compared those who did and did not receive an intraoperative steroid. A total of 74 patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Two RCTs (Corcoran et al 2021a;Shang et al 2022) compared wound dehiscence, no patient developed wound dehiscence in the two RCTs, so there were no statistical differences between groups. Only one cohort study (Egan et al 2019) investigated wound dehiscence, the follow-up time was 90 days, and showed no between-group differences (P < 0.05).…”
Section: Effect Of Dexamethasone On Wound Infection and Dehiscencementioning
confidence: 99%
See 4 more Smart Citations
“…Two RCTs (Corcoran et al 2021a;Shang et al 2022) compared wound dehiscence, no patient developed wound dehiscence in the two RCTs, so there were no statistical differences between groups. Only one cohort study (Egan et al 2019) investigated wound dehiscence, the follow-up time was 90 days, and showed no between-group differences (P < 0.05).…”
Section: Effect Of Dexamethasone On Wound Infection and Dehiscencementioning
confidence: 99%
“…The full versions of 41 articles were retrieved after screening and conducting a detailed selection process. Finally 16 articles (Nazar et al 2011;Tien et al 2016;Nazar et al 2009;Corcoran et al 2021a;Backes et al 2013;Purushothaman et al 2018;Zhang et al 2014;Shang et al 2022;Wasfie et al 2018;Herbst et al 2020;Godshaw et al 2019;Allen et al 2020;Egan et al 2019;Harding et al 2021;O'Connell et al 2018;Corcoran et al 2021b) met the inclusion criteria and underwent data extraction. The details of the screening procedure are shown in Fig.…”
Section: Literature Search and Retrievalmentioning
confidence: 99%
See 3 more Smart Citations